2015
DOI: 10.1111/nph.13643
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for extensive parallelism but divergent genomic architecture of adaptation along altitudinal and latitudinal gradients in Populus trichocarpa

Abstract: SummaryAdaptation to climate across latitude and altitude reflects shared climatic constraints, which may lead to parallel adaptation. However, theory predicts that higher gene flow should favor more concentrated genomic architectures, which would lead to fewer locally maladapted recombinants.We used exome capture to resequence the gene space along a latitudinal and two altitudinal transects in the model tree Populus trichocapra. Adaptive trait phenotyping was coupled with F ST outlier tests and sliding window… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 75 publications
5
84
0
Order By: Relevance
“…Holliday et al . () compared signatures of selection in populations of Populus trichocarpa in two mountain ranges in British Columbia and found evidence for convergent evolution in 23% of the SNPs under selection in loci generally involved in developmental and light‐mediated processes.…”
Section: Resultsmentioning
confidence: 99%
“…Holliday et al . () compared signatures of selection in populations of Populus trichocarpa in two mountain ranges in British Columbia and found evidence for convergent evolution in 23% of the SNPs under selection in loci generally involved in developmental and light‐mediated processes.…”
Section: Resultsmentioning
confidence: 99%
“…A better understanding of the genetic regulation of adaptation is fundamental for the development of adequate management and conservation strategies under a changing climate (Porth et al., 2015). In recent years, population genomics has been used to study tree populations, identifying genes under selection involved in local adaptation (Evans et al., 2014; Geraldes et al., 2014; Holliday et al., 2016; Zhou et al., 2014). The great advantage of population genomics studies over smaller‐scale population genetics studies is that the former allow identifying and correcting for genomewide demographic effects, increasing the power to detect locus‐specific effects (Stinchcombe & Hoekstra, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The Populus trichocarpa genome, the first tree to be sequenced (Tuskan et al., 2006), created numerous opportunities for pioneering genomic studies in tree species. Several genomewide association, transcriptome, and population genomics studies have been reported for P. trichocarpa , contributing to the current knowledge about the species regulation of complex traits (McKown, Klápště, et al., 2014; Porth et al., 2013a, 2013b), extent of linkage disequilibrium (LD) and effective population size (Slavov et al., 2012; Zhou, Bawa, & Holliday, 2014), population structure (Geraldes et al., 2014; Slavov et al., 2012; Zhou et al., 2014), genetic diversity (Evans et al., 2014; Zhou et al., 2014), demographic history (Zhou et al., 2014), adaptation (Evans et al., 2014; Geraldes et al., 2014; Holliday, Zhou, Bawa, Zhang, & Oubida, 2016; Porth et al., 2015; Zhou et al., 2014), and sex determination (Geraldes et al., 2015). Studies in other poplar species (Stölting et al., 2013, 2015; Wang, Street, Scofield, & Ingvarsson, 2016a, 2016b) have significantly lagged behind.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Holliday et al . ), it becomes increasingly important to identify the targets of selection (‘candidate genes’) that can be functionally linked to ecological variables that likely affect the fitness of individuals. A promising approach is to focus on a priori determined candidate genes or gene families that are suspected to underlie important ecotypic traits, as has been demonstrated by Smadja et al .…”
Section: Introductionmentioning
confidence: 99%